2021
DOI: 10.1115/1.4051323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processes of Nanobubbles: Growth, Collapse, and Coalescence

Abstract: Nanobubbles are typically classified as gas/vapor phase cavities in an aqueous solution with a characteristic length of approximately 100 nanometers (nm). The theoretical lifetime of these nanobubbles has been estimated to be less than ~1 microsecond at a diameter of 100 nm based upon the Young-Laplace pressure, but experimental observations have been reported that indicate that they may exist for many hours, or even days. These nanobubbles can be generated by a number of different methods, such as solvent exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…First of all, the contact angle values measured in this study agree with the other previously reported values of water on graphene layers in TEM studies, i.e., in the range of 60°to 90°a t the nanoscale. 13,27 It is worthwhile to point out that some earlier reported nanoscale contact angles by atomic force microscopy (AFM) are larger than 90°, 37,38 which needs to be further clarified in future studies of the intrusive impacts from both TEM and AFM mechanisms in measuring the nanoscale contact angle. Nevertheless, the impact of contact line pinning on nanoscale contact angle is observed in both AFM and TEM studies, 39−41 and the causes of the pinning can result from both chemical and/or geometrical heterogeneities of 2−10 nm in diameter on the graphene sheets, and a small pinning force between 5 and 70 mN/m can pin the contact line of nanobubbles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, the contact angle values measured in this study agree with the other previously reported values of water on graphene layers in TEM studies, i.e., in the range of 60°to 90°a t the nanoscale. 13,27 It is worthwhile to point out that some earlier reported nanoscale contact angles by atomic force microscopy (AFM) are larger than 90°, 37,38 which needs to be further clarified in future studies of the intrusive impacts from both TEM and AFM mechanisms in measuring the nanoscale contact angle. Nevertheless, the impact of contact line pinning on nanoscale contact angle is observed in both AFM and TEM studies, 39−41 and the causes of the pinning can result from both chemical and/or geometrical heterogeneities of 2−10 nm in diameter on the graphene sheets, and a small pinning force between 5 and 70 mN/m can pin the contact line of nanobubbles.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in previous reports of in situ TEM experiments of nanoscale contact angles and nanobubbles, , a graphene liquid cell is assembled by two graphene membranes on TEM grids where distilled water is sandwiched in between, Figure a. The liquid cell is then mounted on a TEM sample holder with a temperature control mechanism and is imaged in a Hitachi H7600 TEM system at a 100 kV electron beam voltage.…”
Section: Methods and Materialsmentioning
confidence: 99%
See 1 more Smart Citation